Waqf Protection in Islamic Jurisprudence and their Judicial Procedures in the Kingdom of Saudi Arabia : A publication issued by Saee Foundation for the Development of Waqfs (7) (مجلة وقف في دراسات الاوقاف, 2026)
Origin of the book: A thesis submitted in fulfillment of the requirements for the PhD Degree in comparative jurisprudence, the Higher Judicial Institute, at Al-Imam Muhammad Bin Saud Islamic University  The researcher talked about the waqf protection from its jurisprudential and judicial aspects, and supported that by the visibility of the judicial system in the Kingdom of Saudi Arabia in waqf protection through courts of various levels and the instruments issued by them.  The researcher started with the introduction which included an explanation of the waqf protection and the legitimacy of it, the definition of the assault on waqfs and its prohibition, and the date of the assault on waqfs. Through the first title in which he talked about aspects of waqf protection, including five chapters: The first included: Documentation and declaration. The second included: superintendence over the waqf. The third included: Disposition of waqfs. The fourth included: Maintaining the endowed property from assault. The fifth included: waqf investment and development. Each chapter has included a number of scientific researches and issues. Through the second title in which he talked about judicial procedures of waqf protection, including three chapters: The first included: Judicial procedures of waqf protection in the Kingdom of Saudi Arabia, including: Proving them of all types, assigning superintendents over them, holding them accountable, and methods of settling their disputes. The second included judicial decisions associated with assault on waqfs, including: Guarantee of waqfs, penalty, superintendent dismissal and disposition nullification. The third included: Judicial applications from the courts of the Kingdom of Saudi Arabia.